How phloem-feeding insects face the challenge of phloem-located defenses - Will, Torsten; Furch, Alexandra C.; Zimmermann, Matthias R. (Frontiers in Plant Science, 2013)
Due to the high content of nutrient, sieve tubes are a primary target for pests, e.g. most phytophagous hemipteran. To protect the integrity of the sieve tubes as well as their content, plants possess diverse chemical and physical defense mechanisms. The latter mechanisms are important because they can potentially interfere with the food-source accession of phloem-feeding insects. Physical defense mechanisms are based on callose as well as on proteins and often plug the sieve tube. Insects that feed from sieve tubes are potentially able to overwhelm these defense mechanisms using their saliva. Gel saliva forms a sheath in the apoplast around the stylet and is suggested to seal the stylet penetration site in the cell plasma membrane. In addition, watery saliva is secreted into penetrated cells including sieve elements; the presence of specific enzymes/effectors in this saliva is thought to interfere with plant defense responses. Here we detail several aspects of plant defense and discuss the interaction of plants and phloem-feeding insects. Recent agro-biotechnological phloem-located aphid control strategies are presented.